Intellectual property rights, the WTO and developing countries : the TRIPS agreement and policy options (Zed Books LondonGB, 2000)
Addresses the main issues, provides bibliographic sources for further research and seeks to stiimulate independent thinking on the implicaitions of the TRIPS Agreement in Develping Countries. Includes the Report of an Expert Group on the TRIPS Agreement and Develping Countries, which provides guidance to developing countries on ways of implementing the said Agreement in manner consistent with development needs.
Keywords: INTELLECTUAL PROPERTY